HUBUNGAN DUKUNGAN SOSIAL SUAMI DENGAN EFIKASI DIRI ISTRI DALAM MENJALANI MASA MENOPAUSE - Rohmah, Fayakun Nur; Ismarwati, Ismarwati (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background :Yogyakarta has an olderly population structure (pre-elderly and elderly) women among most other provinces in Indonesia that means the majority number of women is in menopause . Every woman has different response and complaints that occurred before and after menopause. Good self-efficacy will help women to face the complaints toward menopause. Objectives : This research aimed to analyze the correlation between husband’s support and woman’s self-efficacy towards menopause from a female perspective. Methods : This research was a correlational study with cross sectional approach. The sample technique of this study was accidental sampling technique, with the number of 32 women in menopause as the samples. Data were analyzed with Chi-square. Result  :As the result, p-value was 0.378 (p>0.05). Conclusion : There were no correlation between husband’s support and women’s self efficacy towards menopause. Keyword : Menopause, self efficacy, husband support